Comparative evaluation of ketamine - propofol, fentanyl - propofol and butorphanol-propofol on haemodynamics and laryngeal mask airway insertion conditions - Asha Gupta; Sarabjit Kaur; Joginder Pal Attri; Nisha Saini (Wolters Kluwer Medknow Publications, 2011)
Background:Laryngeal mask airway is a non invasive supraglottic device which has led to a radical change in the management of modern general anaesthesia. Propofol as a single agent is unsatisfactory and to overcome problems associated with LMA insertions. In the present study, we evaluated the haemodynamic changes and laryngeal mask airway insertion conditions comparing ketamine and opioids as adjuncts to propofol. Patients and Methods: 90 patients were randomly divided into 3 groups of 30 each. In Group PK-ketamine 0.5mg kg -1, in Group PF-fentanyl 1ug kg -1 and in Group PB - butorphanol 20ug kg -1 was given intravenously immediately before induction with propofol 2.5 mg kg -1 . Jaw relaxation was assessed according to Young's criteria and the overall conditions according to modified Scheme of Lund and Stovener. Results: The mean total dose of propofol required in Group PK was 160.37 ± 15.75mg, in Group PF 156.22 ± 17.18 mg and in Group PB 140.08 ± 18.97 mg. The incidence of absolute jaw relaxation was highest in Group PB (93.33%) patients, intermediate in Group PF (53.33%) patients and lowest in Group PK i.e. 36.66% patients. Excellent insertion conditions were observed in 12 (40%) patients in Group PK and 13 (43.33%) patients in Group PF and in 26 (86.67%) patients in Group PB. Group PK showed more rise in systolic and diastolic blood pressure and heart rate post LMA insertion as compared to Group PF and Group PB. Conclusion: It is concluded that addition of butorphanol to propofol for LMA insertion provided absolute jaw relaxation and excellent insertion conditions with stable haemodynamics Side effects like coughing, gagging, lacrimation and laryngospasm were lower as compared to the other two groups.